Lasting alteration of spatial orientation induced by passive motion in rabbits and its possible relevance to mal de débarquement syndrome - Maruta, Jun (Frontiers in Neurology, 2023)
Mal de débarquement syndrome (MdDS) is a chronic disorder of spatial orientation with a persistent false sensation of self-motion, whose onset typically follows prolonged exposure to passive motion of a transport vehicle. Development of similar but transient after-sensations mimicking the exposed motion and associated postural instability, indicative of central vestibular adaptation, are common. The cause of MdDS is thought to be a subsequent failure to readapt to a stationary environment. However, vestibular plasticity pertinent to this illness has not been studied sufficiently. Because rabbit’s eye movement is sensitive to three-dimensional spatial orientation, characterizing maladaptation of the vestibulo-ocular reflex (VOR) induced in the animal may open an approach to understanding MdDS. Three rabbits underwent a series of two-hour conditioning with an unnatural repetitive motion that involved a complex combination of roll, pitch, and yaw movements in a head-based reference frame, consisting of periodic rolling in darkness in a frame of reference that rotated about an earth-vertical axis. Eye movement in three dimensions was sampled during the conditioning stimulus as well as during test stimuli before and up to several days after conditioning. During roll-while-rotating conditioning, the roll component of the VOR was compensatory to the oscillation about the corresponding axis, but the pitch component was not, initially prominently phase-leading the head pitch motion but subsequently becoming patently phase-delayed. Unidirectional yaw nystagmus, weak but directionally compensatory to the earth-vertical axis rotation, was seen throughout the period of conditioning. After conditioning, simple side-to-side rolling induced an abnormal yaw ocular drift in the direction that opposed the nystagmus seen during conditioning, indicating a maladaptive change in spatial orientation. The impact of conditioning appeared to be partially retained even after one week and could be partially reversed or cumulated depending on the rotation direction in the subsequent conditioning. The observed reversible long-term maladaptation of spatial orientation as well as the depth of knowledge available in relation to the vestibular cerebellar circuits in this species support the potential utility of a rabbit model in MdDS research.